Disharmonization of Integrated Rehabilitation Policy for Narcotics Users from a Justice Perspective - Ramadhany Nasution (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Drug abuse in Indonesia constitutes a multidimensional problem that extends beyond criminal law to encompass public health, social welfare, and human rights. Although statutory regulations have recognized medical and social rehabilitation as the primary mechanisms for the recovery of drug users, their implementation continues to be dominated by punitive approaches through imprisonment. This condition reflects a lack of harmony within the integrated rehabilitation policy, resulting in legal uncertainty and the failure to achieve substantive justice. This study aims to analyze the forms of disharmony in rehabilitation policies for drug users and to formulate a reconstruction model of criminal law policy grounded in justice. The research employs a normative juridical method using statutory, conceptual, and analytical approaches. The findings demonstrate that policy disharmony occurs in three principal dimensions: legal substance, which still reflects a dualism between punitive and rehabilitative paradigms; institutional structure, characterized by overlapping authorities and weak inter-agency coordination; and legal culture, which remains predominantly punishment-oriented. Consequently, rehabilitation has not yet become the primary response for drug users suffering from addiction. This study proposes a justice-based integrated rehabilitation model through regulatory harmonization, strengthening integrated assessment as the basis for legal decision-making, implementing diversion to rehabilitation, reinforcing restorative justice, and integrating legal, health, and social systems. This model represents the study's conceptual contribution to supporting the reconstruction of a more humane, effective, and recovery-oriented criminal law policy capable of promoting legal certainty, protecting human rights, and establishing a more equitable system for addressing drug abuse.